The Effect Of Economic Growth And Inflation On Value Added Tax Revenue In ASEAN Countries With Foreign Direct Investment As a Moderation - Tricahyono, Danang; Wijaya, Suparna (Educoretax, 2024)
Goods and Services Tax or also known as Value Added Tax is one of the taxation systems implemented by many countries around the world. The VAT system has been implemented in most ASEAN member countries with various rates. This study aims to analyze the effect of economic growth and inflation on VAT revenue in ASEAN countries in the period 2012 to 2019. In addition, this study will also examine the effect of foreign investment as a moderating variable. The analysis method used is panel data multiple linear regression analysis. The results showed that the GDP and FDI variables had a positive and significant effect on VAT revenue and the CPI variable had a negative and significant effect on VAT revenue. Furthermore, FDI weakens the relationship between economic growth and VAT revenue and FDI does not affect the relationship between inflation and VAT revenue. Due to the limited availability of data, it is expected that future research can use more comprehensive and up-to-date data so that it can be more accurate and relevant in analyzing the factors that affect VAT revenue in ASEAN countries.